Pengaruh Kebijakan Dividen, Kebijakan Hutang dan Nilai Pasar terhadap Investment Opportunity Set (pada Perusahaan Manufaktur Sub Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia, Periode 2014-2017) - Rahmi Zilla Aulia; Rina Asmeri; Meri Yani (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2019)
The aim of the study is to determine the effect of Dividend Policy, Debt Policy and Market Value on the Investment Opportunity Set. The research was carried out at the textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The population in this study was all textile and garment sub-sector manufacturing companies listed on the IDX. The total population of companies listed in this study were 17 companies. Sampling of this study using purposive sampling technique, thus the final sample obtained was 9 companies incorporated in the textile and garment sector on the Indonesia Stock Exchange for the period of 2014-2017. The data analysis technique used in this study is descriptive analysis, classic assumption test, multiple linear regression and hypothesis testing using the coefficient of determination, t-statistics to examine the partial regression coefficient and f-statistics to examine the regression coefficient simultaneously with the help of SPSS 21 for windows. The results show that dividend policy has a significant effect on the investment opportunity set, debt policy has a partial effect on the investment opportunity set, market value partially influences the investment opportunity set and dividend policy, debt policy and market value simultaneously influence the investment opportunity set .